Community Health Immersion Programs in Medical Institutions - Borkar Sonali; Petkar Prithvi; Shrivastava Prateek Saurabh; Mendhe Harshal Gajanan; Bandre Gulshan (Wolters Kluwer Medknow Publications, 2024)
Exposure to the local community is crucial and pivotal to deliver contextual learning to medical students and thereby aid in the process of attaining subject-specific competencies. In the field of medical education, community health immersion refers to a set of systematic and immersive educational experiences for medical students to expose them to sociocultural and health-related attributes of the general population. Community health immersion has been linked with multiple merits that are crucial in the making of a competent medical graduate, who is well equipped to deliver patient-centered care. Even though there are multiple benefits to community health immersion nevertheless, its implementation in the community might vary based on institutional support and local community-related factors. There is an immense need to overcome these challenges to ensure optimal benefit, and this will essentially require the adoption of a multipronged approach with the help of all the concerned stakeholders.